Hubungan Konsumsi Makanan Kariogenik dan Kejadian Karies Gigi pada Anak Usia Sekolah di Desa Wori (e-GiGi, 2023)
Abstract: Dental caries is the most common non-communicable disease worldwide. Children's teeth are prone to dental caries due to immature tooth growth and children’s behavior in maintaining oral health, such as high consumption of cariogenic foods. This study aimed to determine the relationship between cariogenic food consumption and the incidence of dental caries among school-age children in Desa Wori. This was an analytical and observational study with a cross-sectional design. Sampling using stratified random sampling technique obtained 153 children aged 6-12 years as respondents. Data collection was carried out by filling out the Food Frequency Questionnaire (FFQ) checklist to obtain cariogenic food consumption and examination of their teeth using the International Caries Detection and Assessment System (ICDAS) to detect whether or not dental caries in the children. The results showed that 83.66% of respondents consumed high cariogenic foods and 79.08% of respondents had dental caries. Data analyzed using the chi-square test obtained a p-value of 0.002 (p